Methodology of Forensic Linguistic Analysis in Criminal Insult Investigations - T. Izotova; V. Kuznetsov; A. Plotnikova (Теория и практика судебной экспертизы)
A summary of the methodology covers the theoretical underpinnings of forensic linguistic analysis in cases involving criminal insult, as well as methods of achieving forensic objectives. A full-text print version of the methodology is planned for release later this year.